2011
DOI: 10.5432/jjpehss.10024
|View full text |Cite
|
Sign up to set email alerts
|

Empirical study on the effectiveness of the TPSR model in a junior high school class

Abstract: Empirical study on the eŠectiveness of the TPSR model in a junior high school class. Japan J. Phys. Educ. Hlth. Sport Sci. 56: 157 172, June, 2011 AbstractThe purpose of this study was to examine the eŠectiveness of Hellison's TPSR model, which was developed in the USA. The validity of the TPSR model was examined in a physical education class for 3rd year male students at a public junior high school. To conˆrm the eŠect of the TPSR model, a single case experimental design was used, switching between base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Hellison and Walsh (2002) reviewed research papers that examined the eŠects of the TPSR model and reported that it increased students' awareness of their self-repression, self-managing and assistance to others, increased their communication skills in PE classes, and facilitated improvement of their human relations. In Japan, Umegaki et al (2006) and Umegaki et al (2011) reported that the TPSR model facilitated the improvement of university students' and junior high school students' social skills.…”
Section: Introductionmentioning
confidence: 99%
“…Hellison and Walsh (2002) reviewed research papers that examined the eŠects of the TPSR model and reported that it increased students' awareness of their self-repression, self-managing and assistance to others, increased their communication skills in PE classes, and facilitated improvement of their human relations. In Japan, Umegaki et al (2006) and Umegaki et al (2011) reported that the TPSR model facilitated the improvement of university students' and junior high school students' social skills.…”
Section: Introductionmentioning
confidence: 99%